Response Surface Methodology Optimization of Concrete Strength Using Hydroxyapatite Nanopowder as Admixture - muhamad, mimi suliza; Osman, Mohd Hairi; Mohamad, Mohd Yasser Ridzuan Nizam; Sunar, Norshuhaila Mohamed; Ali, Roslinda; Hamidon, Nuramidah; Abdul Hamid, Nor Hazren; Harun, Hasnida (Progress in Engineering Application and Technology, 2020)
Conventional method that utilize chemical admixture in concrete is not sustainable to the environment. Nowadays, the use of natural hydroxyapatite (HAp) as admixture in concrete is getting attention. This study aim to optimize the compressive and tensile strength of concrete at various HAp dose and time by using response surface methodology (RSM). The modelling and statistical analyses was conducted via historical data design based on experimental data obtained in previous study. The polynomial regression equation was found to provide the best fit for the model, with a coefficient of regression of 0.99. The analysis of variance indicate that the models were significant. The actual and predicted values plots of compressive and tensile strength shows good correlation. In addition, the individual and synergistic effects of the HAp dose and time on the compressive and tensile strength of concrete were analysed using 3D surface plot. The results obtained indicate that 21% HAp dose and 28 days are the optimum working parameters to achieve a maximum compressive and tensile strength of 48.9 and 8.1 MPa, respectively. It was observed that the model prediction values accurately matched the experimental values for tensile strength and within 1% matched for compressive strength. The results of this study demonstrate that RSM is a robust tool that can used for process optimization of concrete performances.